2021
DOI: 10.1101/2021.02.19.431936
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishment of a human three-dimensional chip-based chondro-synovial co-culture joint model for reciprocal cross-talk studies in arthritis research

Abstract: Rheumatoid arthritis is characterised by a progressive, intermittent inflammation at the synovial membrane, which ultimately leads to the destruction of the synovial joint. The synovial membrane, which is the joint capsule's inner layer, is lined with fibroblast-like synoviocytes that are the key player supporting persistent arthritis leading to bone erosion and cartilage destruction. While microfluidic models that model molecular aspects of bone erosion between bone-derived cells and synoviocytes have been es… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Previous studies have identified many physicochemical and biological factors, including protein coating of crystals, that play a proinflammatory or anti-inflammatory role in gouty arthritis, under specific temporal and spatial conditions, adding to the heterogeneity of gouty arthritis 31 39. Therefore, future research that uses cartilage organoid or even intraarticular assessments is necessary 40 41. In addition, evaluating cartilage-derived factors in different phases such as asymptomatic hyperuricaemia with MSU crystal deposition, intercritical gout and gout flares can help us better understand the role of CII under various temporal and tissue conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified many physicochemical and biological factors, including protein coating of crystals, that play a proinflammatory or anti-inflammatory role in gouty arthritis, under specific temporal and spatial conditions, adding to the heterogeneity of gouty arthritis 31 39. Therefore, future research that uses cartilage organoid or even intraarticular assessments is necessary 40 41. In addition, evaluating cartilage-derived factors in different phases such as asymptomatic hyperuricaemia with MSU crystal deposition, intercritical gout and gout flares can help us better understand the role of CII under various temporal and tissue conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Humanized mice also tend to be more frequently used nowadays, they however remain very expensive and have numerous limitations 24 . In the quest toward the development of new models in which human physiology would be even better represented 25 , new approaches have emerged and have been improved over the last decade, especially around the concepts of organoids and/or organ-on-a-chip 26 . 3D tissue engineering approaches that mimic structural features of the joint or microfluidic approaches have for example been recently discussed 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…(C) Design of the osteochondral microfluidic model that includes encapsulated IPSCs in order to form bone and cartilage tissue [Adapted from ( 107 )]. (D) Design of the organoid-based joint-on-a-chip co-culture system that includes chondral and synovial organoids [Adapted from ( 108 )]. (E) i: Real picture of the cartilage-on-chip model and overview of the encapsulated chondrocytes in a hydrogel scaffold; ii: stimulation for the diffusion of biomolecules through circular chamber and channel (Adapted from ( 109 ).…”
Section: Advanced 3d Models: Microfluidic Technologiesmentioning
confidence: 99%
“…These systems allow to move forward on studies regarding intravasation of surrounding tissues and to understand how blood vessels affect the behaviour of fibroblast-like synoviocytes and macrophages in the arthritic joint. A recently published study by Rothbauer et al aimed to understand the crosstalk between synovium and cartilage tissue of arthritic joint ( 108 ). Here, for the first time, a patient-derived dual organoid model was successfully established by co-culturing primary human synovial fibroblast obtained from RA patients and commercial human primary chondrocytes ( Figure 3D ).…”
Section: Advanced 3d Models: Microfluidic Technologiesmentioning
confidence: 99%